Influences of Solubility and Vehicle Carriers on Eriodictyol Pharmacokinetics in Rats - Manthey, John A.; Ferreira, Paula S. [UNESP]; Cesar, Thais B. [UNESP] (American Chemical Society (ACS), 2022)
In this study, the pharmacokinetics of oral doses of eriodictyol in 1% sodium carboxymethylcellulose and in saline/PEG400/Tween80 (75/20/5, v/v/v) in rats were compared. The pharmacokinetics of eriocitrin administered as a dissolved solution in water were also characterized. Metabolites of eriodictyol and eriocitrin in whole blood consisted mainly of eriodictyol, homoeriodictyol, and hesperetin glucuronides and ring-fission metabolites. In whole blood, no free nonconjugated flavanone aglycones were detected. Significant differences were observed in the pharmacokinetics of eriodictyol administered as a suspension in 1% sodium carboxymethylcellulose versus administration as a dissolved solution in saline/PEG400/Tween80 (75/20/5, v/v/v). At a dose of 25 mg kg-1eriodictyol administered with 1% sodium carboxymethylcellulose, a biphasic pharmacokinetic curve was observed, while only a single concentration peak was observed following an administration of 25 mg kg-1eriodictyol dissolved in saline/PEG400/Tween80 (75/20/5, v/v/v). For all trials, the pharmacokinetics of eriodictyol differed from those of eriocitrin dissolved in water.
Keywords: eriocitrin; flavanones; glucuronides; metabolites; sulfated metabolites